Analysis of User Satisfaction Regarding Service Quality Dimensions in Teleconsultations - Flores-Dianderas, Katherine Roxana; Falcon Flores, Kristel Milagros; Méndez-Gutiérrez, Leidy Lucia (LACCEI, 2024)
The study focused on analyzing user satisfaction regarding the dimensions of teleconsultation service quality, considering both public hospitals and private clinics. A quantitative approach was utilized, with a non-experimental and cross-sectional design, collecting data through surveys from a sample of 315 individuals. The analysis was conducted using SPSS 29 and Excel software. The results showed that the dimensions of service quality (tangible elements, reliability, responsiveness, security, and empathy) have a significant correlation with user satisfaction, with a regression model explaining 45.8% of the variance. Specifically, the study revealed that most users rated the dimensions of reliability and responsiveness positively, while security was evaluated at a medium level. Compared to international studies, a high acceptance and satisfaction with telemedicine services were observed, similar to the results obtained in Lima. However, there are still segments of the population that prefer in-person consultations, suggesting the need for a hybrid approach to maximize patient satisfaction. These findings underscore the necessity of continually improving teleconsultations to meet user expectations. In conclusion, telemedicine in Lima has proven to be an effective and wellaccepted tool by users, although challenges persist in certain areas.